Effect of climate change on Aspergillus flavus and aflatoxin B1 production - Medina, Angel; Rodriguez, Alicia; Magan, Naresh (Frontiers in Microbiology, 2014)
This review considers the available information on the potential impact of key environmental factors and their interactions on the molecular ecology, growth and aflatoxin production by Aspergillus flavus in vitro and in maize grain. The recent studies which have been carried out to examine the impact of water activity x temperature on aflatoxin biosynthesis and phenotypic aflatoxin production are examined. These have shown that there is a direct relationship between the relative expression of key regulatory and structural genes under different environmental conditions which correlate directly with aflatoxin B1 production. A model has been developed to integrate the relative expression of 10 biosynthetic genes in the pathway, growth and aflatoxin B1 (AFB1) production which was validated under elevated temperature and water stress conditions. The effect of interacting conditions of aw x temperature x elevated CO2 (2x and 3x existing levels) are detailed for the first time. This suggests that while such interacting environmental conditions have little effect on growth they do have a significant impact on aflatoxin biosynthetic gene expression (structural aflD and regulatory aflR genes) and can significantly stimulate the production of AFB1. While the individual factors alone have an impact, it is the combined effect of these three abiotic factors which have an impact on mycotoxin production. This approach provides data which is necessary to help predict the real impacts of climate change on mycotoxigenic fungi.